General internists' beliefs, behaviors, and perceived barriers to routine HIV screening in primary care. - Korthuis, P Todd; Berkenblit, Gail V; Sullivan, Lynn E; Cofrancesco, Joseph; Cook, Robert L; Bass, Michael; Bashook, Philip G; Edison, Marcia; Asch, Steve M; Sosman, James M (AIDS education and prevention : official publication of the International Society for AIDS Education, 2011)
The Centers for Disease Control and Prevention (CDC) recommends routine HIV screening in primary care but little is known about general internists' views of this practice. We conducted a national, cross-sectional, Internet-based survey of 446 general internists in 2009 regarding their HIV screening behaviors, beliefs, and perceived barriers to routine HIV screening in outpatient internal medicine practices. Internists' awareness of revised CDC guidelines was high (88%), but only 52% had increased HIV testing, 61% offered HIV screening regardless of risk, and a median 2% (range 0-67%) of their patients were tested in the past month. Internists practicing in perceived higher risk communities reported greater HIV screening. Consent requirements were a barrier to screening, particularly for VA providers and those practicing in states with HIV consent statutes inconsistent with CDC guidelines. Interventions that promote HIV screening regardless of risk and streamlined consent requirements will likely increase adoption of routine HIV screening in general medicine practices.
Keywords: Adult; Attitude of Health Personnel; Centers for Disease Control and Prevention (U.S.); Cross-Sectional Studies; General Practitioners; Guideline Adherence; Health Services Accessibility; HIV Infections; Humans; Internet; Logistic Models; Male; Middle Aged; Physician's Practice Patterns; Practice Guidelines as Topic; Primary Health Care; Societies, Medical; United States